Phytotoxic activity of auxin on germination and seedling growth of Stylosanthes humilis - Cardoso, Danúbia Gonçalves (2015)
Although auxins, at high concentrations, are well known for their effects on plant growth control, little is known about their effects during seed-to-seedling transition. This study was carried out to evaluate the modulation of ethylene biosynthesis and metabolic adjustment in response to auxin during seed germination and postgermination growth of Stylosanthes humilis. In freshly harvested seeds (dormant seeds) of S. humilis, auxin, at high concentration, repressed the 1-aminocyclopropane-1-carboxylic acid (ACC) oxidase activity. On the other hand, ACC biosynthesis and ethylene production by seedlings were increased by auxin treatments, which was associated with seedling growth inhibition. Furthermore, auxin inhibited ACC biosynthesis in aged seeds (non-dormant seeds). Together, these data indicate that the effect of high levels of auxin in the control of ethylene metabolism is developmentally separated. In addition, 2,4-dichlorophenoxyacetic acid (2,4-D) induced secondary dormancy in aged seeds of S. humilis, which was associated with the operation of energy-saving metabolism. Moreover, secondary dormancy of 2,4-D treated seeds was broken by ACC solution. Thus, this study has revealed a process in which storage reserves mobilization and ethylene crosstalk in regulating the developmental transition from metabolic quiescent seed to actively growing seedling.